Tribes in transition : Indian Christians reflect on the original inhabitants of the land : a SAIACS consultation - Hrangkhuma, F.; Chand, Padmini; Wood, Beulah; Hiebert, Paul (Bangalore, SAIACS Press, 2004)
Papers presented at a SAIACS consultation held during 29-31 January 2003
Keywords: Christianity.-- Influence, Congresses; Christianity and culture.-- India, Congresses; India; Tribes.-- India.-- Religion, Congresses; Conference papers and proceedings